Five-year follow-up of a phase I trial of donor-derived modified immune cell infusion in kidney transplantation - Schaier, Matthias; Morath, Christian; Wang, Lei; Kleist, Christian; Opelz, Gerhard; Tran, Thuong Hien; Scherer, Sabine; Pham, Lien; Ekpoom, Naruemol; Süsal, Caner; Ponath, Gerald; Kälble, Florian; et al. (Frontiers in Immunology, 2023)
Background. The administration of modified immune cells (MIC) before kidney transplantation led to specific immunosuppression against the allogeneic donor and a significant increase in regulatory B lymphocytes. We wondered how this approach affected the continued clinical course of these patients. Methods. Ten patients from a phase I clinical trial who had received MIC infusions prior to kidney transplantation were retrospectively compared to 15 matched standard-risk recipients. Follow-up was until year five after surgery. Results. The 10 MIC patients had an excellent clinical course with stable kidney graft function, no donor-specific human leukocyte antigen antibodies (DSA) or acute rejections, and no opportunistic infections. In comparison, a retrospectively matched control group receiving standard immunosuppressive therapy had a higher frequency of DSA (log rank P = 0.046) and more opportunistic infections (log rank P = 0.033). Importantly, MIC patients, and in particular the four patients who had received the highest cell number 7 days before surgery and received low immunosuppression during follow-up, continued to show a lack of anti-donor T lymphocyte reactivity in vitro and high CD19+CD24hiCD38hi transitional and CD19+CD24hiCD27+ memory B lymphocytes until year five after surgery. Conclusions. MIC infusions together with reduced conventional immunosuppression were associated with good graft function during five years of follow-up, no de novo DSA development and no opportunistic infections. In the future, MIC infusions might contribute to graft protection while reducing the side effects of immunosuppressive therapy. However, this approach needs further validation in direct comparison with prospective controls. Trial registration. EudraCT Number: 2014-002086-30, ClinicalTrials.gov Identifier: NCT02560220 (for the TOL-1 Study)